2021
DOI: 10.3390/jcm10245868
|View full text |Cite
|
Sign up to set email alerts
|

Medialized versus Lateralized Center of Rotation in Reverse Total Shoulder Arthroplasty: A Systematic Review and Meta-Analysis

Abstract: One of the original biomechanical principles of reverse total shoulder arthroplasty (RTSA) is medialization of the center of rotation (COR) relative to the native level of the glenoid. Several authors have proposed the lateralized center of rotation, which is characterized by a lateralized (L) glenoid and medialized (M) humeral component. The aim of this review is to compare the clinical and functional outcomes of COR in medialized (M-RTSA) and lateralized (L-RTSA) RTSA in patients with uniform indications and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…They also found that lateralized versus medialized RSA had lower rates of scapular notching (6.6% vs. 47.7%, P<0.01) and postoperative infection (1% vs. 7.7%, P=0.01). Berton et al [ 3 ] used stricter inclusion and exclusion criteria in their study compared to Cho et al, [ 5 ] and their work was more similar to the present study, as they included studies reporting on patients with indications limited to cuff tear arthropathy, irreparable cuff tear, or cuff tear associated with osteoarthritis. Although Berton et al [ 3 ] also excluded studies including patients undergoing revision RSA or an indication of rheumatoid arthritis, acute fracture, post-traumatic fracture sequelae, tumor, or active infection, the authors only required 1 year of follow-up.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…They also found that lateralized versus medialized RSA had lower rates of scapular notching (6.6% vs. 47.7%, P<0.01) and postoperative infection (1% vs. 7.7%, P=0.01). Berton et al [ 3 ] used stricter inclusion and exclusion criteria in their study compared to Cho et al, [ 5 ] and their work was more similar to the present study, as they included studies reporting on patients with indications limited to cuff tear arthropathy, irreparable cuff tear, or cuff tear associated with osteoarthritis. Although Berton et al [ 3 ] also excluded studies including patients undergoing revision RSA or an indication of rheumatoid arthritis, acute fracture, post-traumatic fracture sequelae, tumor, or active infection, the authors only required 1 year of follow-up.…”
Section: Discussionmentioning
confidence: 96%
“…Berton et al [ 3 ] used stricter inclusion and exclusion criteria in their study compared to Cho et al, [ 5 ] and their work was more similar to the present study, as they included studies reporting on patients with indications limited to cuff tear arthropathy, irreparable cuff tear, or cuff tear associated with osteoarthritis. Although Berton et al [ 3 ] also excluded studies including patients undergoing revision RSA or an indication of rheumatoid arthritis, acute fracture, post-traumatic fracture sequelae, tumor, or active infection, the authors only required 1 year of follow-up. Since ROM is known to continue to improve up to 2 years postoperatively [ 52 ], the findings of Berton et al [ 3 ] may not accurately represent the full improvement that occurs with lateralized implants.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations